Professional Burnout of Higher Education Teachers: - Sergey ZAKHARIA; Oksana KURTEVA; Olga SHCHUKINA (ACROSS, 2025)
The problem of emotional burnout of higher education teachers is a consequence of constant exposure to stressogenic factors and has negative consequences affecting the physical state of the teacher, psychological and emotional spheres. The article analyses the problems and identifies constructive ways of solution: from preventive measures to optimisation of working conditions of a higher education teacher, which can have a beneficial effect on both external and personal factors of emotional burnout in professional activity.